A new reversal mode in exchange coupled antiferromagnetic/ferromagnetic disks: distorted viscous vortex1. Issue 21 (7th June 2015) - Gilbert, Dustin A.; Ye, Li; Varea, Aïda; Agramunt-Puig, Sebastià; del Valle, Nuria; Navau, Carles; López-Barbera, José Francisco; Buchanan, Kristen S.; Hoffmann, Axel; Sánchez, Alvar; Sort, Jordi; Liu, Kai; et al.
<x xml:space="preserve">Abstract</x> Ferromagnetic dots coupled to a thin antiferromagnet reverse via a distorted viscous vortex state.